International Connections of Russian Regions and the Centre’s Position: Evolution of Coordination - S. P. Arteev (Vestnik MGIMO-Universiteta)
Review of the book by Logvinova I.V. Coordination of International and Foreign Economic Connections of the Russian Federation’s regions. Moscow, MGIMO, 2018. 238 p. (In Russian).